Investigação de julgamentos metacognitivos de informantes múltiplos sobre o desempenho de idosos em tarefas de memória - Gonçalves, Maria Clara Miceli (Universidade Federal de São Carlos, 2018)
This study aims to investigate metacognitive monitoring, laying emphasis on the metamemory of the elderly, through the analysis of relationships between performance estimated by them and their actual performance in standardized tasks that evaluate the operational memory; as well as to verify the relationship of the judgments of people close to the elderly regarding the performance demonstrated by them in the standardized tasks and the actual performance of the elderly in these tasks. The participants were 30 elderly people, both genders, aged between 65 and 90 years, and a person close to each one of them, totaling 60 participants. The subtests Arithmetic, Digits and Sequences of Numbers and Letters of the WAIS-III were introduced to the elderly along with a sheet with questions about their judgment of whether the items were correct. The Senior Metacognition Scale (EMETA-S) for evaluation of metacognitive abilities and the Mental State Mini-Exam (MMSE) as a means of indicating signs of dementia were also applied. To verify the judgments of people close to the elderly regarding the performance demonstrated by them in the standardized tasks, a scale composed of 23 questions was used that mention day-to-day situations related to short-term memory capacity and working memory, which were evaluated by subtests. The results of the subtests were correlated to a score obtained by the elderly in the EMETA-S and the answers related to the judgments of the elderly and the people close to the performance of the elderly in the three subtests. Strong and significant correlations were found at 0.01 between the judgments and the actual performance for the three subtests (Arithmetic r = 0.80, Digits, r = 0.66 and Sequence of Numbers and Letters r = 0.77) and moderate correlations and significant at 0.01 between judgments of close people and actual performance of the elderly in the WAIS-III subtests (Arithmetic r = 0.49, Digits r = 0.41, Sequence of Numbers and Letters r = 0.49). The results indicate that the elderly, caregivers and family members may be judging adequately the performance of memory tasks. Participants with more than 8 years of study tended to estimate their results more accurately compared to participants with less than 8 years of schooling. On the other hand, no significant differences were found in the age-group variable.
Keywords: Metamemória; Envelhecimento; Capacidades cognitivas; Desempenho real; Desempenho estimado; Metamemory; Elderly; Cognitive capacities; Actual performance; Estimated performance; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA